Evolution of Plant P-Type ATPases - Pedersen, Christian N.; Axelsen, Kristian B.; Harper, Jeffrey F; Palmgren, Michael G. (Frontiers in Plant Science, 2012)
Five organisms having completely sequenced genomes and belonging to all major branches of green plants (Viridiplantae) were analyzed with respect to their content of P-type ATPases encoding genes. These were the chlorophytes Ostreococcus tauri and Chlamydomonas reinhardtii, and the streptophytes Physcomitrella patens (a non-vascular moss), Selaginella moellendorffii (a primitive vascular plant), and Arabidopsis thaliana (a model flowering plant). Each organism contained sequences for all five subfamilies of P-type ATPases. Whereas Na+ and H+ pumps seem to mutually exclude each other in flowering plants and animals, they co-exist in chlorophytes, which show representatives for two kinds of Na+ pumps (P2C and P2D ATPases) as well as a primitive H+-ATPase. Both Na+ and H+ pumps also co-exist in the moss P. patens, which has a P2D Na+-ATPase. In contrast to the primitive H+-ATPases in chlorophytes and P. patens, the H+-ATPases from vascular plants all have a large C-terminal regulatory domain as well as a conserved Arg in transmembrane segment 5 that is predicted to function as part of a backflow protection mechanism. Together these features are predicted to enable H+ pumps in vascular plants to create large electrochemical gradients that can be modulated in response to diverse physiological cues. The complete inventory of P-type ATPases in the major branches of Viridiplantae is an important starting point for elucidating the evolution in plants of these important pumps.